Textual criteria for selecting media texts in Arabic language teaching books for non-native speakers (Damascus University Journal of arts and humanities sciences, 2026)
The aim of the research was to build a list of textual standards for selecting media texts in Arabic language teaching books for non-native speakers, and then to identify the degree to which they are achieved in these books.The research adopted the descriptive analytical approach and represented the original community of the research, all series of teaching Arabic to non-native speakers. The researcher chose four (4) series from them; for their availability, their inclusion of media texts, their comprehensiveness, and their fulfillment of Arabic language skills. The sample for the research included (26) written media texts, and the research tools were represented by a list of textual standards and a form for analyzing the content of media texts in these series.The study reached a set of results, the most important of which was: Thedegree of achievement of textual standards in media texts in Arabic language teaching series for non-native speakers was (large).The standards came in terms of the degree of verification in the following order (Informativity in first place, then acceptability in second place, intentionality in third place, Situationality in fourth place, and Cohesion in fifth place with a very high degree of verification, while Coherence came in sixth place with an acceptable degree of verification, and intertextuality in seventh place with a weak degree of verification).
Keywords: Standards; Textual Standards; Media Texts; Arabic language Teaching Books For Non-Native Speakers; Non-Native Speakers